Factors That Influence the Implementation of Nursing Care Process in Internal Medicine Men and Women at HNGV Dili Year 2022 - Ana do Rosário de Jesus Leite; Maximiano Oqui; Miguel Soares; Maria Manuela Alves; José da Conceição Ximenes; Serafino de Almeida Oqui (Rifa'Institute, 2023)
Introduction: The implementation of the nursing care process is concerned by nursing professional globally to implement in the health facility, based on the operational standard of nursing progress start by assessment, nursing diagnostic, planning intervention, implementation, and evaluation. Methods: This researcher uses a quantitative cross-sectional analytical approach which will be carried out the nurses in internal men and women HNGV Dili. Nonprobability sampling technique uses questionnaire, analyzes data uses Spearman Rank and Chi Square formula. Objective: The purpose of this study to find out the factors that influences the implementation of nursing care process. Results and Discussion: Of the 52 respondents the results that apply nursing care process 84.6% and does not apply nursing care process 15.4%, good knowledge 25%, sufficient knowledge 21.2%, less knowledge 53.8%, heavy service volume 80.8% and light service volume 19.2%. applies the service team 78.8% and does not apply 21.2%. Conclusion: The test Spearman Rank the results influence between knowledge with implementation nursing care process 0.377 with significant value 0.006<0.05. there is influence between the volume of service and implementation nursing care process (P Value 0.016<0.05). has influence between team services with implementation nursing care process (P Value 0.030<0.05).